REPRESENTASI PEREMPUAN DALAM FILM DESPICBALE ME 3 MELALUI KARAKTER LUCY WILDE - Varadila Permata Putri Prastowo; Nadia Qisthina Putri (Jurnal Komunikasi dan Kajian Media, 2019)
Mass Media can  be used to spread ideology in a wide and effective range. In fact,cartoon film can also be a tool to disseminate feminist value through women's representationwhen carrying out their gender roles. Feminism is a movement and ideology that stands up torights and equality between a man and woman in politics, economics, culture, or even inpublic and domestic sphere. Public sphere and domestic sphere are examples from genderrole by modern women who have feminist values According to the focus of this research,which is the character of Lucy in Despicable Me 3, her character is reflecting a gender rolein public and domestic sphere. This research uses descriptive method with semiotic analysisby Pierce. Semiotics used is semiotics Peirce by looking at representamen consisting of icons,indexes, and symbols in each scene that presents the value of liberal feminism on the Lucy’scharacter. The study concludes that there are three gender roles performed by Lucy'scharacter as a career woman, wife, and also a mother. In running every gender role she hasthe value of liberal feminism.